A case report of toxic epidermal necrolysis associated with AZD-9291 - Wang J; Cheng XY; Lu Y; Zhou BR (Dove Medical Press, 2018)
Jie Wang, XianYe Cheng, Yan Lu, BingRong Zhou Department of Dermatology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, The People’s Republic of China Abstract: Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) are a strain of small molecule inhibitors mainly used to treat the metastatic non-small cell lung cancer. Their predominant adverse effect is skin toxicity, usually manifested as acneiform rash, skin fissure, xerosis, and paronychia. Severe epidermal necrosis and exfoliation rarely occur. As one of the new generation of epidermal growth factor receptor-tyrosine kinase inhibitors, AZD-9291 is claimed to have better efficacy and fewer side effects, particularly appropriate for patients with EGFR T790M mutation. Herein we report a 51-year-old man who developed a large area of skin necrosis and was diagnosed with toxic epidermal necrolysis after AZD-9291 ingestion. Keywords: TEN, AZD-9291, osimertinib, EGFR-TKIs, NSCLC